Pengaruh Profitabilitas, Kebijakan Hutang DanKepemilikan Manajerial Terhadap Nilai Perusahaan(Studi Pada Perusahaan Manufaktur Di Bursa Efek Indonesia Tahun 2011-2013) - Pertiwi, Tria Yunnara Kusuma, Drs. Sri Padmantyo, MBA (2016)
This study aims to examine Influence Profitability , Managerial Ownership Policy Against Debt and Corporate Value Study on manufacturing companies listed in Indonesia Stock Exchange 2011-2013 . The sampling technique in this research is using purposive sampling technique is a method of sampling that takes an object with certain criteria . The independent variables are profitability , debt policy and managerial ownership , while the dependent variable is the value of the company . Samples used in this study were 26 manufacturing companies with a time period of 3 years ( 2011-2013 ) so that the overall amount of data as many as 78 companies . Data obtained from the financial statements and a summary of the performance of the company which was published in Indonesian Capital Market Directory ( ICMD ) . The analytical tool used is multiple linear regression analysis using SPSS 21. The hypothesis is done by using the F test , t test and the coefficient of determination . Classic assumption test used in this study is a test for normality , autocorrelation test , multikolinearitas test and heteroskedastisitas test . The results of data analysis showed that simultaneous profitability ( ROA ) positive effect on the value of the company while the debt policy ( DER ) and the managerial ownership and no significant negative effect on firm value .